MEASUREMENT OF THE TERRESTRIAL ANDANTHROPOGENIC RADIONUCLIDE CONCENTRATIONS IN BAFRA KIZILIRMAK DELTA (BIRD SANCTUARY) IN TURKEY - Turhan, Şeref; Mutuk, Halil; Gümüş, Hasan (Radiation Protection Dosimetry (2014), Vol. 158, No. 3, pp. 350–354, 2013)
In this study, the activity concentrations of terrestrial and anthropogenic radionuclides in the soil samples collected from Bafra Kızılırmak Delta were measured by using gamma spectrometry with an NaI(Tl) detector. The average values of activity concentrations of 238U, 232Th and 40K were found to be 37.2+2.8, 33.7+3.1 and 413.0+59.8 Bq kg21, respectively. 137Cs was also measured in some samples. It has a mean value of 13.8+1.0 Bq kg21. From the activity concentrations, the absorbed gamma dose rates in outdoor and the corresponding annual effective dose rates and external hazard index (Hex) were estimated.
Keywords: Measurement,Anthropogenic